2020
DOI: 10.1021/acsmedchemlett.0c00472
|View full text |Cite
|
Sign up to set email alerts
|

Complex Crystal Structures of EGFR with Third-Generation Kinase Inhibitors and Simultaneously Bound Allosteric Ligands

Abstract: Osimertinib is a third-generation tyrosine kinase inhibitor (TKI) and currently the gold-standard for the treatment of patients suffering from non-small cell lung cancer (NSCLC) harboring T790M-mutated epidermal growth factor receptor (EGFR). The outcome of the treatment, however, is limited by the emergence of the C797S resistance mutation. Allosteric inhibitors have a different mode of action and were developed to overcome this limitation. However, most of these innovative molecules are not effective as a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Also, most recently growing interest in the development of hybrid compounds for ErbBfamily can be observed in literature. [22][23][24] Examples of the combination of conventional amino quinazoline scaffold plus EAI045-like motifs with reversible binding modus for EGFR showed similar behaviour to our study. While high potency for L858R/T790M/C797S mutation is achieved, they lack efficient selectivity against wt enzyme.…”
Section: Discussionsupporting
confidence: 86%
“…Also, most recently growing interest in the development of hybrid compounds for ErbBfamily can be observed in literature. [22][23][24] Examples of the combination of conventional amino quinazoline scaffold plus EAI045-like motifs with reversible binding modus for EGFR showed similar behaviour to our study. While high potency for L858R/T790M/C797S mutation is achieved, they lack efficient selectivity against wt enzyme.…”
Section: Discussionsupporting
confidence: 86%
“…To circumvent acquired drug-resistance against TKIs, a set of allosteric inhibitors targeting EGFR were previously introduced, including EAI001, EAI045, and JBJ-04-125-02 (shortened as “JBJ” in the article) ( Figure 1 E) [ 20 , 42 , 43 , 44 ]. To our knowledge, all current allosteric EGFR inhibitors target the MEK-pocket, which is generated by the outward displacement of the αC-helix and was first identified in mitogen-activated protein (MAP) kinase kinases (MEKs) ( Figure 1 E) [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, this combination treatment has been shown to render EGFR mutant NSCLC cells unable to acquire resistance, likely due to the orthogonal mechanisms of resistance to osimertinib versus the allosteric inhibitor. 60 A second compound class with a dibenzodiazepinone core was discovered in the same screen that led to EAI045. 38 A co-crystal structure with a representative dibenzodiazepinone, DDC4002, demonstrated that these compounds bind the same pocket as EAI045 and its derivatives, with related ligandprotein interactions despite their very different chemical structures (Figure 2I).…”
Section: Egfr-first-generation To Third-generation Inhibitors and Beyondmentioning
confidence: 99%
“…Thus, a unique avenue for treatment may involve combination therapy with a structurally compatible third‐generation TKI such as osimertinib. In preclinical studies, this combination treatment has been shown to render EGFR mutant NSCLC cells unable to acquire resistance, likely due to the orthogonal mechanisms of resistance to osimertinib versus the allosteric inhibitor 60 . A second compound class with a dibenzodiazepinone core was discovered in the same screen that led to EAI045 38 .…”
Section: Egfr—first‐generation To Third‐generation Inhibitors and Beyondmentioning
confidence: 99%